2009
DOI: 10.1111/j.1438-8677.2008.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic integrity of sympatric hybridising plant species: the case ofOrchis italicaandO. anthropophora

Abstract: Plant species diversification entails the action of reproductive barriers, which are severely challenged when related species grow in contact and form hybrid progeny. Orchis italica and O. anthropophora are two related orchid species that produce a known hybrid form, O. xbivonae. Here, we analysed a hybrid zone of these two orchids using molecular analysis and experimental crosses. As molecular tools, we employed both real-time PCR and PCR amplification of nuclear markers to evaluate the occurrence of backcros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Essential conditions for speciation by hybridization are that the hybrid exploits an ecological niche, either the parental one or a totally new one, shows an own reproductive success and produces a sufficient number of seeds (ARNOLD 1997). Compared to parental species, previous study demonstrated that O. xbivonae showed low fruiting values in open-pollinated flowers and the absence of any form of postmating isolation (PELLEGRINO et al 2009). The low levels of reproductive success, the lack of post-zygotic barriers and of F 2 (or later) generations (PELLEGRINO et al 2009) suggest that the mycorrhizal symbiosis imposes no constraints on the survival of hybrids, and that the lack of pollinators appears to strongly limit hybrid fitness, as has previously been reported in parental species (PELLEGRINO et al 2010) and other deceptive orchids (MATTILA and KUITUNEN 2000, PELLEGRINO et al 2005, SMITHSON 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential conditions for speciation by hybridization are that the hybrid exploits an ecological niche, either the parental one or a totally new one, shows an own reproductive success and produces a sufficient number of seeds (ARNOLD 1997). Compared to parental species, previous study demonstrated that O. xbivonae showed low fruiting values in open-pollinated flowers and the absence of any form of postmating isolation (PELLEGRINO et al 2009). The low levels of reproductive success, the lack of post-zygotic barriers and of F 2 (or later) generations (PELLEGRINO et al 2009) suggest that the mycorrhizal symbiosis imposes no constraints on the survival of hybrids, and that the lack of pollinators appears to strongly limit hybrid fitness, as has previously been reported in parental species (PELLEGRINO et al 2010) and other deceptive orchids (MATTILA and KUITUNEN 2000, PELLEGRINO et al 2005, SMITHSON 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In the studied site, Orchis italica and O. anthropophora overlap extensively in their spatial distribution and flowering time (flowering peak between the end of April and the middle of May) and grew together with O. xbivonae (PELLEGRINO et al 2009). …”
Section: Study Area and Orchid Speciesmentioning
confidence: 99%
“…As Cozzolino and Widmer (2005) pointed out, the evolution of sister species is not always accompanied by parallel evolutionary shifts in pollination syndromes; closely related species, when growing sympatrically, sharing flowering periods and pollinator(s), are prone to high opportunities for interspecific hybridization (Van der Cingel 1995;Jersakova et al 2006;Pellegrino et al, 2009). This may be the case with the sympatric G.…”
Section: Can G Eulophioides Hybrid With G Recurvum and G Densiflormentioning
confidence: 99%
“…Species integrity can be maintained by post-zygotic mechanisms (Stebbins, 1958;Coyne and Orr, 1998;Rieseberg and Carney, 1998;Tiffin et al, 2001), as seen in some Mediterranean food-deceptive orchids (Cozzolino et al, 2004(Cozzolino et al, , 2006Scopece et al 2007;Pellegrino et al, 2009), as well as Brazilian deceptive orchids (Silva-Pereira et al, 2007). Late post-zygotic mechanism, e.g., low germination rate and low growth rate or zero growth, may prevent G. eulophioides and G. recurvum from generating viable hybrids.…”
Section: Can G Eulophioides Hybrid With G Recurvum and G Densiflormentioning
confidence: 99%
See 1 more Smart Citation